Reproduction in the greenback grey mullet, Liza subviridis (Valenciennes, 1836) - Chan, E.H.; Chua, T.E. (Wiley, 1980)
This paper presents data on the reproductive biology of Liza subviridis, a little studied mullet species. The fish is heterosexual, exhibiting external fertilization. Six maturity stages can be macroscopically identified in the testes and seven in the ovaries. The macroscopic changes in the gonads are manifestations of histological changes occurring in the development of sperm cells and oocytes. First sexual maturity is attained in the length ranges of 9.5–11.5 cm and 10.5–11.5 cm in male and female fish respectively. The fecundity for fish measuring 10.3–13.9 cm in standard length ranged from 40 000–145 000 eggs. The relationship between fecundity (F) and length (L) can be represented as: F= 1.9044 L4.2998. The spawning duration in L. subviridis is restricted to a short and definite period, with all ripe ova being released within a single spawning act. A pronounced spawning season can be detected to extend from June to November. However, during off‐seasons, some spawning also occurs. The correlations between spawning, rainfall and air temperature is discussed.